LTE RF receiver modeling and each part testing with MATLAB simulink - Fatima Faydhe al azzawi (Institute of Advanced Engineering and Science, 2019)
fourth generation cellular network based on Long Term Evaluation (LTE) air interface. LTE is specifically designed for packet data communications, where the emphasis of the technologies high spectral efficiency, high peak data rates, low latency, and frequency flexibility. In this paper a LTE physical layer design and implemented using MATLAB codes and Simulink, where MATLAB codes generate the 64 QAM transmitting signal and simulating LTE frames while Simulink model perform the physical layer which including the band limiting, free space path loss adding, channel, RF receiver, demodulation, 10-bit ADC, DC offset cancellation, saving data to preform EVM measurements, and viewing the spectrum signal after each block, finally QAM with multi –order tested under AWGN.